Konsep Demokrasi Dalam Perspektif Islam dan Barat - Marisa Hasibuan, Ghassani; Qalbi, Habibatul; Tarisha Lingke Lubis; Falerizki, Iqbal; Rasyid, Faidhul (Albayan Journal of Islam and Muslim Societies, 2025)
Democracy is a system of government that emphasizes people's participation in the decision-making process. Although often associated with the Western world, democratic values are also found in Islamic teachings through the concept of shura (deliberation), justice, and trustworthy leadership. This article compares the concept of democracy from an Islamic and Western perspective in terms of philosophical basis, sources of law, highest authority, and political goals. In Islam, the highest sovereignty lies in the hands of Allah with the Qur'an and Sunnah as sources of law, while in Western democracy, sovereignty lies in the hands of the people with laws established through majority consensus. This study aims to examine and compare the concept of democracy from an Islamic and Western perspective, and to examine the relevance of both in the context of modern government. The method used is a library research with a descriptive qualitative approach, which examines primary and secondary literature related to the principles of democracy in both perspectives. The results of the study show that although Western democracy is rooted in the values of secularism and rationality, while Islamic democracy is based on revelation and sharia, both have common ground in terms of people's participation, social justice, and accountability of leaders. However, the striking differences lie in the source of legitimacy of power and the limits of individual freedom. In conclusion, democracy in Islam and the West can complement each other if understood contextually and implemented by paying attention to local and universal values that uphold justice and the welfare of the people.